(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
This study aimed to determine the leven of the teacher preparation program qualityat Quneitra Education Faculty from the Point of View of its Faculty Members in it , To achieve this goal, the researcher used a scale that included (50) criteria distributed on (6) areas according to a five-graded scale, namely: (Student Teachers’ Knowledge, Skills and Attitudes (Programs Offered) - the Assessment and Evaluation System in the College - Practical Education and Field Experiences - Diversity and Individual Differences - Qualification, Performance and Professional Development of Faculty Members - the College Administration and its Resources) , The research sample consisted of (11) members of the Quneitra Education Faculty from Damascus University, The study concluded that the degree of the teacher preparation program qualityat Quneitra Education Faculty from the Point of View of its Faculty Members in it is (Great), and There are also no statistically significant differences in the average degree of verification of the teacher preparation program Qualityat Quneitra Education Faculty from the Point of View of its Faculty Members in it, according to the study variables (Sex - Career Seniority).